The modern mercenary: private armies and what they mean for world order - McFate, Sean (Oxford Univ. Press, 2014)
Peace through profit motive? -- Understanding the private military industry -- A codependency problem -- How did we get here? -- Why private armies have returned -- The murky side of private force -- The modern world order: a brief history -- Neomedievalism -- Neomedieval warfare -- Military enterprisers in Liberia: building better armies -- Mercenaries in Somalia: a neomedieval tale -- Medieval modernity